Comparison of soil strength measurements of agricultural soils in Nebraska. (June 2018) - Wieder, Wendy; Shoop, Sally; Barna, Lynette; Franz, Trenton; Finkenbiner, Catherine
Highlights: Soil strength and water content were measured for three agricultural fields. The light weight deflectometer (LWD) was compared to other standard field strength tests. The LWD results compared best with the Dynamic Cone Penetrometer and Clegg Impact Hammer. Soil water contents were determined both remotely and from soil samples. Correlations showed some effect of soil water content on soil strength. Abstract: In 2014 the University of Nebraska, Lincoln (UNL) was engaged in field testing program to investigate a soil moisture mapping system as a crop management tool. In conjunction with this work, the US Army Engineer Research and Development Center, Cold Regions Research and Engineering Laboratory (ERDC-CRREL) deployed a team to perform soil characterization and strength measurements at three agricultural test sites. The primary objective was an investigation of the Lightweight Deflectometer (LWD) as a soil surface strength tool for the purposes of assessing bearing capacity of soft soils. The LWD measurements were performed with those from more "standard" tests, i.e. the Dynamic Cone Penetrometer, Cone Penetrometer, and Clegg Impact Hammer to determine if the LWD produced results that compared with these methods. The strength test data were also used to calculate California Bearing Ratio (CBR) values using existing equations in order to see if the different test methods produced similar CBR values that could in turn be used to predict the bearing capacity of the sites. The secondary objective was to compare the strength data with the corresponding soil water content data taken by UNL to determine if soil moisture was an indicator of soil strength.